Atoxigenic-based technology for biocontrol of aflatoxin in maize and groundnuts for Tanzania - Mahuku, George; Mauro, A.; Pallangyo, B.; Nsami, E.; Boni, S.; Koyano, E.; Mponda, O.; Ortega Beltran, A.; Atehnkeng, J.; Aquiline, F.; Samuel, R.; Njela, J.; et al. (Wageningen University & Research, 2022)
Application of biocontrol products containing atoxigenic isolates of Aspergillus flavus to reduce aflatoxin content in crops is an effective strategy for managing aflatoxin in several regions throughout the world. We report the development and validation of two aflatoxin biocontrol products, Aflasafe TZ01 and Aflasafe TZ02, for use in maize and groundnut in Tanzania, a country frequently affected by aflatoxin contamination. Each product contains four atoxigenic A. flavus genotypes native and widely distributed in Tanzania. Efficacy tests on maize and groundnut were conducted over two years and in four regions of Tanzania where aflatoxin contamination is prevalent. Application of both products significantly (P<0.05) reduced aflatoxin levels in maize and groundnut in both years and in all districts. No differences were observed in total Aspergillus section Flavi population in treated and untreated fields, revealing that application of the biocontrol products do not alter overall Aspergillus populations in the environment. The results indicate that both products are effective tools for aflatoxin mitigation in groundnut and maize. The products were officially registered in 2018. Currently, there are scale-out and-up efforts of aflatoxin biocontrol products in Tanzania through a private sector company that is making the products available to farmers. Protecting maize and groundnut from aflatoxin contamination in Tanzania can result in health, income, and trade benefits.